Comparative transcriptomic and metabolomic analysis reveals mechanisms of selenium-regulated anthocyanin synthesis in waxy maize (Zea mays L.) - Guo, Guangyu; Wang, Yufeng; Zhang, Baoku; Yu, Haoran; Li, Liang; Cao, Guanglu; Chen, Baicui; Li, Chengxin; Bu, Fanshan; Teng, Song; Yu, Qingtao; Gao, Mingbo; et al. (Frontiers in Plant Science, 2024)
Anthocyanins in maize (Zea mays L.) kernels determine the plant's color and can enhance its resistance. Selenium (Se) significantly impacts plant growth, development, and secondary metabolic regulation. However, the molecular mechanisms by which Se regulates anthocyanin synthesis in waxy corn remain unclear. This study employed integrated transcriptomic and metabolomic analyses to investigate the mechanisms through which selenium influences anthocyanin synthesis in yellow and purple waxy corn. The results showed that maize varieties with higher anthocyanin content had higher selenium enrichment capacity in their kernels.Under selenium stress, HN2025 exhibited 1,904 more differentially expressed genes (DEGs) and 140 more differential metabolites compared to HN5. The expression levels of anthocyanin synthesis-related genes and transcription factors such as phenylalanine ammonia-lyase, flavonoid 3-hydroxylase (F3H), dihydroflavonol reductase (DFR), chalcone synthase (CHS), cinnamate-4-hydroxylase (C4H), anthocyanin 5,3-O-glucosyltransferases, and anthocyanidin reductase, MYB, and bHLH were strongly induced in HN2025. Metabolomic analysis revealed significant enrichment in anthocyanin biosynthesis, flavonoid and flavonol biosynthesis, glutathione metabolism, phenylalanine biosynthesis, and phenylalanine metabolism under selenium treatment. Three up-regulated PAL genes and one C4H gene were significantly enriched with DAMs in phenylalanine metabolism, phenylpropanoid biosynthesis, flavonoid biosynthesis, and anthocyanin biosynthesis, resulting in significant differences between HN5 and HN2025 in selenium-induced anthocyanin metabolism-related pathways. These findings provide a theoretical basis for understanding the effects of selenium on the molecular regulatory mechanisms of anthocyanin biosynthesis in maize kernels.